Relationship between School Education and Economic Growth: SAARC Countries - Hanif, Nadia; Arshed, Noman (International Journal of Economics and Financial Issues, 2016)
For long increasing economic growth is the major objective of macroeconomic policy makers of the country. Many studies have tried to put forward a theory which can explain the pattern of GDP growth, in this series Cobb-Douglass were most prominent in making a production function using physical capital and labor as inputs. But later studies highlighted that human capital is also a significant component of this production function. This study used three proxies for the human capital for the case of SAARC countries to see whether higher proxy has better marginal impact on the growth of the selected countries. The results for dynamic panel data models reveal that tertiary education enrollment has highest impact on growth as compare to primary and secondary education enrollment. Keywords: GDP, Human Capital, Panel cointegration. JEL Classification: I25